Awareness of Cardiovascular Health among Adults Residing in a Municipality in Kathmandu District, Nepal - Subedee, Samiksha; Sharma, Muna (Journal of Karnali Academy of Health Sciences, 2023)
Background: Cardiovascular diseases are the leading cause of high disability adjusted life years and premature death, accounting disability among 43% of cases. If there is public awareness, most of the cardiovascular diseases can be prevented with modification of behavioral risk factors. Therefore, this study was conducted to find out the peoples’ awareness on cardiovascular health.Methods: A cross-sectional design was used. Data was collected using an in-person interview technique among randomly selected 236 adults residing in Budhanilkantha Municipality of Kathmandu District. Semi-structured interview schedule based on WHO Stepwise approach and literature review was used to collect data. Data analyzed using descriptive statistics (frequency, percentage, median, Inter Quartile Range) and inferences were drawn with an application of the chi-square test, and Fisher’s exact test.Results: Among 236 participants, most (85.6%) of the adults had an adequate level of awareness regarding cardiovascular health. However, around 80% of them were unaware of radiating pain as a symptom of heart attack and around 40% of adults did not recognize high blood sugar and dyslipidemia as risk factors of cardiovascular disease. Awareness of cardiovascular health was significantly associated with educational level (p